19. HEALTH STAFF'S WORKING MOTIVATION AT THE NATIONAL HOSPITAL OF ENDOCRINOLOGY IN 2022 (Vietnam Journal of Community Medicine, 2023)
Background: Working motivation is employees’ desire and willingness to work to achieveorganizational goals. For medical facilities, the working motivation of medical staff affects thequality of medical service delivery.Objective: Describe the working motivation of health workers at the National Hospital ofEndocrinology in 2022.Methods: Cross-sectional study, quantitative research.Results: From the analysis of quantitative information from 520 health workers at the NationalHospital of Endocrinology through questionnaires, the research results show that 28.1% of healthworkers have high work motivation, and 71.9% of health workers have usual work motivation. Thetypical average score of work motivation of health workers is 3,89±0,44, which is relatively high,from 3.82 to 3.97 (maximum score is 5).
Keywords: Working motivation; health workers.